Monitoring of Influenza Vaccination Coverage among Pregnant Women in Germany Based on Nationwide Outpatient Claims Data: Findings for Seasons 2014/15 to 2019/20 - Annika Steffen; Thorsten Rieck; Anette Siedler (Vaccines, 2021)
Pregnant women and their infants are at increased risk for severe influenza-related complications. A decade has passed since influenza vaccination was first recommended for pregnant women in Germany in 2010; however, monitoring of vaccination coverage (VC) has not yet been implemented for this target group. Using nationwide outpatient claims data, we here provide results on influenza VC among pregnant women in Germany for seasons 2014/15 to 2019/20. For any given season, pregnant women were defined as women who had undergone prenatal health care in at least two consecutive quarters within a season. VC increased from 9.0% in season 2014/15 to 16.6% in 2019/20 (+84%), while most of the increase occurred from season 2016/17 (VC: 9.9%) onwards (+68%). Consistently across seasons, women in east Germany were 40 to 60% more likely to be vaccinated compared to women residing in west Germany. According to age, the highest VC was observed among women aged 35 to <40 years (2019/20: 18.2%). Despite noticeable increases in influenza VC during recent years, overall coverage remains low among pregnant women. Starting with this analysis, VC among pregnant women in Germany will be monitored on a yearly basis in order to detect trends and identify immunization gaps.